(untitled) (Journal of Problems in Computer Science and Information Technologies, 2026)
Accurate wind speed forecasting plays an important role in the planning, operation, and control optimization of modern wind energy systems. Kazakhstan, the country with the largest wind energy potential in Central Asia, is facing significant challenges due to the highly variable, nonlinear, and non-stationary nature of wind. This study proposes a wind-speed forecasting framework based on frozen pre-trained Transformer backbones (BERT/BART) with lightweight projection-based adaptation for time-series inputs. The study employs frozen pre-trained Transformer backbones with self-attention and lightweight projection-based adaptation of Bidirectional Encoder Representations from Transformers (BERT) and Bidirectional and Auto-Regressive Transformers (BART) as the core of the model. In this retrospective analysis, hourly wind speed data from five representative cities across Kazakhstan are used to evaluate simulated operational forecast performance at seven time steps: 1, 3, 6, 36, 72, 144, and 432 hours. The LLMs were compared with AutoRegressive Integrated Moving Average (ARIMA), Segmented Recurrent Neural Network (SegRNN), and Patch Time Series Transformer (PatchTST) models, and the results showed superior accuracy and higher stability in long-term forecasting. These results support the potential of pre-trained Transformer backbones as effective sequence models for wind-speed forecasting under diverse climatic conditions.